Impact of Heads-Up Displays on Small Unmanned Aircraft System Operator Situation Awareness and Performance: A Simulated Study. Issue 5 (16th March 2022) - Rebensky, Summer; Carroll, Meredith; Bennett, Winston; Hu, Xueyu
ABSTRACT: The purpose of the current study was to examine the effect of two interface types on operator situation awareness (SA), performance, and workload for small Unmanned Aircraft System (sUAS) search and rescue operations in a simulated computer-based task. The first interface type was a simulated, traditional, heads-down display (HDD) in which system information was presented separately from the view of the aircraft and the environment. The second interface type was a simulated, heads-up display (HUDs) in which the system information was overlaid on the environmental view. Results revealed a significant effect of interface type on SA, with the simulated HUD resulting in significantly higher objective SA. Interface type was found to have no significant effect on workload, performance, or subjective SA. Additionally, interactions between the order of display presentation and operator experience level were explored. This paper presents associated methods, results, and implications.